2011
DOI: 10.1074/jbc.m111.298166
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of β-Barrel Assembly Machinery BamCD Protein Complex

Abstract: Background:The Escherichia coli ␤-barrel assembly machinery complex (BamABCDE) facilitates outer membrane protein assembly. Results:The unstructured N terminus of BamC binds and blocks the proposed substrate-binding pocket on BamD. Conclusion:The unstructured N terminus of BamC is essential for BamCD interaction. Significance: The first Bam lipoprotein complex structure reveals how BamC and BamD interact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 41 publications
4
89
0
Order By: Relevance
“…Sam35 and BamD share no obvious sequence homology but perform the same receptor-like function in binding unfolded substrates at the surface of the membrane into which those substrates are inserted (21,30); therefore, the conservation of the β-barrel assembly mechanism extends beyond the steps performed by BamA. Previous reports demonstrating that some mitochondrial β-barrels can be assembled in bacteria and that some bacterial OMPs can be assembled in mitochondria implied that the assembly complexes have similar substrate recognition mechanisms (40)(41)(42)(43), and structural studies (13)(14)(15)(44)(45)(46) suggested that BamD might recognize OMP substrates based on its homology to proteins that bind C-terminal peptides (e.g., a component of the mitochondrial translocase, Tom70; a peroxisomal protein receptor, PEX5; and a factor responsible for organizing Hsp chaperone proteins, Hop). Our results connect these observations and provide the underlying molecular basis for substrate recognition, which explains the reciprocity of β-barrel assembly between mitochondria and bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sam35 and BamD share no obvious sequence homology but perform the same receptor-like function in binding unfolded substrates at the surface of the membrane into which those substrates are inserted (21,30); therefore, the conservation of the β-barrel assembly mechanism extends beyond the steps performed by BamA. Previous reports demonstrating that some mitochondrial β-barrels can be assembled in bacteria and that some bacterial OMPs can be assembled in mitochondria implied that the assembly complexes have similar substrate recognition mechanisms (40)(41)(42)(43), and structural studies (13)(14)(15)(44)(45)(46) suggested that BamD might recognize OMP substrates based on its homology to proteins that bind C-terminal peptides (e.g., a component of the mitochondrial translocase, Tom70; a peroxisomal protein receptor, PEX5; and a factor responsible for organizing Hsp chaperone proteins, Hop). Our results connect these observations and provide the underlying molecular basis for substrate recognition, which explains the reciprocity of β-barrel assembly between mitochondria and bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism by which β-barrel assembly proceeds is only beginning to be elucidated. Structures of the components of the bacterial β-barrel assembly machine (BamA-E) have been determined recently, and several hypotheses about how they facilitate the assembly of its substrates have been proposed (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The β-barrel component BamA contains a kinked β-strand, which might allow substrate proteins to be inserted by passing laterally from the lumen of the BamA β-barrel into the hydrophobic membrane (18).…”
mentioning
confidence: 99%
“…High-resolution structures of all four Bam lipoproteins of E. coli have also been solved (14,16,15,18,25,35). These structures suggest that some of the lipoproteins may also interact with the ␤-barrel OMP substrates (14,15,35), although experimental data supporting this notion are lacking. Unlike BamBCE, BamD is present in almost all members of Proteobacteria and has been shown to be essential in E. coli (21,26) and Neisseria meningitidis (42).…”
mentioning
confidence: 86%
“…For example, N. meningitidis appear to lack BamB [72]. Representative structures of all the components of the BAM complex have now been solved and have been instrumental in guiding ongoing research [7][8][9]60,[73][74][75][76][77][78][79][80][81][82] (figure 3).…”
Section: Outer Membrane Protein Delivery To the B-barrel Assembly Macmentioning
confidence: 99%